How are Tuvalu’s Children Developing? Evidence-based Policy Recommendations for Better Early Childhood Development of Tuvaluan Children - Brinkman, Sally (World Bank, Washington, DC, 2019)
This brief presents findings from a census of the early development of Tuvalu’s children, identifies areas of need, and puts forth recommendations to address gaps in service delivery to provide every child in Tuvalu with the best start in life. Universal health care and education are essential in supporting a strong and healthy development of Tuvalu’s citizens. Access to quality health care services and the opportunity to participate in quality Early Childhood Care and Education (ECCE) provides children with the foundation they need to be ready to learn at school. The Government of Tuvalu has invested heavily in health and education, health care is free for all citizens and education is free for those aged 3-18 years. As such, encouragingly the country exhibits few disparities in access to health and education services, including that for children. For example, boys and girls have equitable access to pre-primary education, and policy mandates that ECCE centers cater to the needs of children with special needs. The Pacific Early Age Readiness and Learning (PEARL) program funding by the Global Partnership for Education (GPE), implementing by the World Bank, provides technical assistance and analytical work to improve the participating country’s evidence-base on school readiness and early grade literacy to inform short and medium-term policy agendas, including baseline survey on school readiness and early grade reading levels and piloting interventions. Herein, this brief presents data regarding the status of children’s early health and development, as well as their participation in preschool and their learning environments at home. At a country level, this evidence will help to inform intervention strategies and policy planning in early childhood to strengthen the ECCE system with the goal of ensuring thatall children in Tuvalu reach their developmental potential.